Organic and inorganic compound crystal (H11C4N2) CdI3 as well as preparation method and application thereof

By preparing the organic-inorganic hybrid crystal (H11C4N2)CdI3, the performance deficiencies of existing second-order nonlinear optical crystal materials in laser frequency conversion and phase modulation are solved, achieving efficient second-order nonlinear optical effects and phase matching, which is suitable for nonlinear optical devices.

CN121473002APending Publication Date: 2026-02-06FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310577105.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing second-order nonlinear optical crystal materials are insufficient to meet higher physical and chemical performance requirements in applications such as laser frequency conversion and phase modulation, especially in terms of laser intensity modulation and phase matching.

Method used

A novel organic-inorganic hybrid crystal (H11C4N2)CdI3 is provided, which is prepared by hydrothermal method. It has a monoclinic crystal structure and specific unit cell parameters, which enhances optical anisotropy and realizes efficient second-order nonlinear optical effects. The powder SHG coefficient is 6 times that of KH2PO4 and can achieve phase matching.

Benefits of technology

This crystal exhibits a strong frequency doubling effect under 1064 nm laser irradiation, significantly improving the SHG coefficient and achieving phase matching. It also has high transmittance and thermal stability, making it suitable for nonlinear optical devices such as laser frequency converters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121473002A_ABST
    Figure CN121473002A_ABST
Patent Text Reader

Abstract

The invention discloses an organic and inorganic compound crystal (H11C4N2) CdI3 as well as a preparation method and application thereof. The organic and inorganic compound crystal is a hybrid crystal, the chemical formula is (H11C4N2) CdI3, the organic and inorganic compound crystal belongs to a monoclinic system, the space group is Cc, and the cell parameters are as follows: a = 14.36-14.38, b = 7.13-7.15, c = 13.77-13.79, alpha = gamma = 90 degrees, beta = 121.2-121.4 degrees, and Z = 4. The crystal is prepared by a hydrothermal method. The organic-inorganic hybrid crystal has excellent second-order nonlinear optical performance, can output very strong 532 nm laser under 1064 nm laser irradiation, has a powder SHG coefficient 6 times that of KH2PO4 (KDP), can realize phase matching, and is a second-order nonlinear optical material with potential application value.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a nonlinear optical crystal material, a preparation method and applications thereof, and belongs to the field of nonlinear optical materials. BACKGROUND

[0002] Second-order nonlinear optical crystals are a kind of functional materials widely used in the field of optoelectronic technology, which can realize laser frequency conversion, laser intensity and phase modulation, and holographic storage of laser signals.

[0003] The second-order nonlinear optical crystals currently used in practical applications include LiB3O5 (LBO), β -BaB2O4 (BBO), KH2PO4 (KDP), KTiOPO4 (KTP), AgGaS2 (AGS), etc. With the development of laser technology and the emergence of tunable lasers, nonlinear optical devices have developed rapidly, and laser frequency doubling, mixing, parametric oscillation and amplification; electro-optic modulation, deflection, Q-switching and photorefractive devices have emerged one after another. These researches and applications have put forward more and more requirements on the physical and chemical properties of nonlinear optical materials, and have also promoted the rapid development of nonlinear optical materials. Second-order nonlinear optical crystal materials must have a non-centrosymmetric structure. SUMMARY

[0004] According to one aspect of the present application, the present application provides an inorganic compound crystal (H 11 C4N2)CdI3. The series of crystals exhibit strong frequency doubling effect, and the powder SHG coefficients are 6 times that of KH2PO4 (KDP), and can realize phase matching, which are nonlinear optical materials with potential application value.

[0005] The inorganic compound crystal (also referred to as an organic-inorganic hybrid crystal in the present application) is characterized in that the chemical formula of the inorganic compound crystal is (H 11 C4N2)CdI3, belongs to a monoclinic system, and the space group is Cc , the unit cell parameters are a = 14.3~14.5Å, b = 7.1~7.3 Å, c = 13.7~13.9 Å, α = γ = 90°, β = 120~122°, Z = 4.

[0006] Optionally, a 14.36~14.38 Å, b = 7.13~7.15 Å, c= 13.77~13.79 Å, α = γ =90°, β = 121.2~121.4°.

[0007] Alternatively, the cell parameters are: a = 14.368-14.369 Å, b =7.134~7.136 Å, c =13.777~13.779 Å, with preferred unit cell parameters as follows: a = 14.3680(6) Å, b = 7.13490(10) Å, c = 13.7778(5) Å, α = γ = 90°, β =121.298(5)°, Z = 4.

[0008] The inorganic compound crystal (H) 11 The crystal structure of C4N2)CdI3 is as follows: Figure 1 As shown. Figure 1 (a) and (b) in the diagram are schematic diagrams of the coordination environment of piperazine ligands and cadmium atoms. Figure 1 (c) in the diagram is a schematic projection of the crystal structure along the b-axis. It can be seen that each C or N atom on the piperazine ligand is tetracoordinated, indicating that they all belong to sp... 3 Hybridization. Each Cd atom is coordinated with three I atoms and one N atom from a piperazine ligand, forming a distorted CdNI3 tetrahedron. From Figure 1 As shown in (c), the polarizations of each CdNI3 tetrahedron cancel each other out along the b-axis, but cooperate along the ac-plane. This arrangement is beneficial for increasing the optical anisotropy of the compound, thereby enhancing its second-order nonlinear optical coefficient.

[0009] Optionally, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 285~295 nm.

[0010] Optionally, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 289 nm.

[0011] Optionally, the inorganic compound crystal has a powder SHG coefficient that is 3 to 12 times that of KH2PO4 under 1064 nm laser irradiation, and can achieve phase matching.

[0012] Optionally, the inorganic compound crystal has a powder SHG coefficient of 6 times that of KH2PO4 under 1064 nm laser irradiation, and can achieve phase matching.

[0013] Optionally, the inorganic compound crystal has a weight loss of no more than 1% at 285°C.

[0014] According to another aspect of the present application, a preparation method of the above inorganic compound crystal is provided, characterized in that a hydrothermal method is used to prepare a raw material mixture containing a piperazine ligand, a cadmium element, an iodine element, an HI aqueous solution, and water, and crystallization is performed at a crystallization temperature of 80-150°C for no less than 6 hours.

[0015] Optionally, in the raw material mixture, the molar ratio of the piperazine ligand, the cadmium element, the iodine element, and water is: H2C4N2: Cd: I: H2O = 1: 0.05-5: 1-400: 1-400.

[0016] Optionally, in the raw material mixture, the molar ratio of the piperazine ligand, the cadmium element, the iodine element, and water is: H2C4N2: Cd: I: H2O = 1: 0.1-2: 5-100: 10-200.

[0017] Optionally, in the raw material mixture, the molar ratio of the piperazine ligand, the cadmium element, the iodine element, and water is: H2C4N2: Cd: I: H2O = 1: 0.3-0.8: 10-50: 50-150.

[0018] Optionally, in the raw material mixture, the piperazine ligand is at least one of piperazine, piperazine hydrochloride, piperazine iodate, piperazine bromate, piperazine carbonate, and piperazine phosphate.

[0019] Optionally, the carbon element is from the piperazine.

[0020] Optionally, in the raw material mixture, the cadmium element is at least one of cadmium oxide, cadmium chloride, cadmium bromide, cadmium iodide, cadmium nitrate, cadmium carbonate, and cadmium sulfate.

[0021] Optionally, the vanadium element is from the CdO.

[0022] Optionally, in the raw material mixture, the iodine is at least one of cadmium iodide and an HI aqueous solution.

[0023] Optionally, the iodine element is from an HI aqueous solution of 55wt%-58wt%.

[0024] Preferably, the concentration of the HI aqueous solution is 57wt%.

[0025] Optionally, the crystallization temperature is 80-150℃, and the crystallization time is not less than 6 hours.

[0026] Optionally, the crystallization temperature is 90-130℃, and the crystallization time is 30-120 hours.

[0027] As a preferred embodiment, the method for preparing the inorganic compound crystal comprises the following steps: (a) placing a raw material mixture containing a piperazine ligand, a cadmium element, an iodine element, and water in a high-pressure reactor, and crystallizing at a crystallization temperature of 80-150℃ for more than 24 hours after being sealed; (b) after the crystallization is completed, lowering the system to room temperature at a cooling rate of not more than 15℃ / h, and the obtained solid sample after being separated and dried is the inorganic compound crystal.

[0028] Optionally, the cooling rate in step (b) is 0.5-13℃ / h.

[0029] Optionally, the cooling rate in step (b) is 0.5-6℃ / h.

[0030] As a preferred embodiment, the method for preparing the inorganic compound crystal comprises the following steps: (a) placing a raw material mixture containing a piperazine ligand, a cadmium element, an iodine element, and water in a high-pressure reactor, and crystallizing at a crystallization temperature of 80-150℃ for more than 24 hours after being sealed; (b) after the crystallization is completed, lowering the system to room temperature at a cooling rate of not more than 15℃ / h, and the obtained solid sample after being separated and dried is the inorganic compound crystal.

[0031] The inorganic compound crystal prepared by the hydrothermal method has a morphology of colorless block crystal.

[0032] According to another aspect of the present application, the inorganic compound crystal is provided as an application of a nonlinear optical crystal material. The second-order nonlinear optical crystal material contains the inorganic compound crystal and / or the inorganic compound crystal prepared according to any of the above methods. The material can output very strong 532 nm laser under 1064 nm laser irradiation, and the powder SHG coefficient is 6 times that of KH2PO4 (KDP), and phase matching can be achieved.

[0033] According to another aspect of the present application, a laser frequency converter is provided, which contains the nonlinear optical crystal material.

[0034] The beneficial effects of the present application include but are not limited to: (1) The application provides a new organic-inorganic hybrid (H 11 The (H 11 C4N2)CdI3 crystal has a conversion rate of 6 times that of KH2PO4 (KDP) under 1064 nm laser irradiation, and can achieve phase matching. Therefore, the (H 11 C4N2)CdI3 crystal has good potential utilization value as a second-order nonlinear optical material.

[0035] (2) The inorganic compound crystal (H 11 C4N2)CdI3 provided by the application has a high transmittance in a 280-800 nm spectral range, and an ultraviolet absorption cutoff wavelength of about 289 nm.

[0036] (3) The inorganic compound crystal (H 11 C4N2)CdI3 provided by the application has high thermal stability and can be stabilized to 289 DEG C.

[0037] (4) The application also provides a preparation method of the organic-inorganic hybrid (H 11 C4N2)CdI3 crystal, which adopts a hydrothermal crystallization method to grow a colorless (H 11 C4N2)CdI3 crystal. The method is simple in process, and can obtain the organic-inorganic hybrid (H 11 C4N2)CdI3 crystal material with high purity and high crystallinity. BRIEF DESCRIPTION OF DRAWINGS

[0038] Figure 1 is a schematic diagram of a crystal structure of the organic-inorganic hybrid (H 11 C4N2)CdI3; wherein (a) is a piperazine ligand; (b) is a Cd atom coordination environment; and (c) is a projection of the crystal structure on an ac plane.

[0039] Figure 2 is an ultraviolet-visible-near infrared diffuse reflectance spectrum of sample 1 # The X-ray diffraction spectrum obtained by fitting the crystal structure analyzed according to single crystal X-ray diffraction is compared with the spectrum obtained by X-ray diffraction test after sample 1 # is ground into powder.

[0040] Figure 3 is an ultraviolet-visible-near infrared diffuse reflectance spectrum of sample 1 # .

[0041] Figure 4 is a thermogravimetric graph of sample 1 # .

[0042] Figure 5 is a SHG signal graph of sample 1 # compared with KDP. DETAILED DESCRIPTION

[0043] The application will be described in greater detail below with reference to the embodiments. However, the application is not limited to these embodiments.

[0044] The raw materials in the embodiments of the application are commercially available unless otherwise specified.

[0045] Example 1 Hydrothermal synthesis of samples

[0046] Piperazine H 10 C4N2, cadmium oxide CdO, HI (concentration of 57 wt%), and water were mixed into raw materials in a certain molar ratio, placed in a polytetrafluoroethylene-lined high-pressure reaction kettle, then heated to a crystallization temperature, and after constant temperature for a period of time, the temperature of the system was reduced to room temperature at a certain cooling rate. After washing by suction filtration, a yellow rod-shaped crystal sample was obtained, which was the sample of the inorganic compound crystal.

[0047] The sample number, raw material type and amount, crystallization temperature and holding time, and cooling rate are shown in Table 1.

[0048] Table 1

[0049] Example 2 Crystal structure analysis Single crystal X-ray diffraction and powder X-ray diffraction methods were used to analyze the structure of sample 1 # ~5 # .

[0050] Among them, single crystal X-ray diffraction was performed on an XtaLAB Synergy-DW CCD type X-ray single crystal diffractometer of RIGAKU Corporation, Japan. The data collection temperature was 293 K, the diffraction light source was graphite monochromatized Cu- Kα ray (λ = 1.54184 Å), and the scanning mode was ω -2 θ ; the data was corrected for absorption using the Multi-Scan method. The structure analysis was completed using the SHELXTL-97 program package; the positions of the heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; and the coordinates of all atoms and anisotropic thermal parameters were refined using the full matrix least squares method based on F 2 .

[0051] Powder X-ray diffraction was performed on an Ultima IV type X-ray powder diffractometer of RIGAKU Corporation, Japan, and the test conditions were fixed target monochromatic light source Cu- Kα, wavelength 1.540598 Å, voltage current 30 kV / 15 A, scanning range 10~70 º, scanning step 0.02 º.

[0052] wherein the single crystal X-ray diffraction results show that the sample 1 # ~5 # with the chemical formula (H 11 C4N2)CdI3 belongs to monoclinic system, and the space group is Cc , and the cell parameters are a = 14.3~14.5 Å, b = 7.1~7.3 Å, c = 13.7~13.9 Å, α = γ = 90°, β = 120~122°, Z = 4. The crystal structure of the organic-inorganic hybrid crystal (H 11 C4N2)CdI3 is shown in Figure 1 . Figure 1 , (a) and (b) are the coordination environment schematic diagrams of piperazine and Cd atoms respectively, Figure 1 , (c) is a projection schematic diagram of the crystal structure along the b-axis direction. It can be seen that each C or N atom on the piperazine ligand is tetrahedrally coordinated, indicating that they all belong to sp 3 hybridization. Each Cd atom is coordinated with three I atoms and one N atom from the piperazine ligand, forming a distorted CdNI3 tetrahedron. From Figure 1 , (c), we can see that the polarization of each CdNI3 tetrahedron cancels out along the b-axis direction, but cooperates along the ac plane. This arrangement is conducive to increasing the optical anisotropy of the compound, thereby enhancing its second-order nonlinear optical coefficient.

[0053] Taking the sample 1 # as a typical representative, the molecular formula is (H 11 C4N2)CdI3, which belongs to monoclinic system, and the space group is Cc , and the cell parameters are a = 14.369~14.369 Å, b = 7.134~7.136 Å, c = 13.777~13.779 Å, α = γ = 90°, β = 121.29~121.31°.

[0054] The powder X-ray diffraction results show that the sample 1 # ~5 #On the XRD spectrum, the peak positions are basically the same, but the peak intensities of each sample are slightly different.

[0055] With sample 1 # As a typical example, such as Figure 2 As shown, based on the crystal structure resolved by single-crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with that of sample 1. # The X-ray diffraction patterns obtained after grinding the samples into powder showed consistent peak positions and intensities, indicating that the obtained samples all had high purity.

[0056] Example 3: Frequency doubling test experiment and results With sample 1 # As a representative, for (H) 11 C4N2)CdI3 was subjected to frequency multiplication testing.

[0057] The specific steps are as follows: A 1064 nm wavelength laser generated by a Q-switched Nd:YAG solid-state laser with a frequency converter is used as the fundamental frequency light to irradiate the crystal powder under test. The generated second harmonic is detected using a photomultiplier tube, and the harmonic intensity is displayed on an oscilloscope. The crystal sample under test is sieved using a standard sieve to obtain crystals of different particle sizes: 45-53 µm, 53-75 µm, 75-105 µm, 105-150 µm, 150-210 µm, and 210-300 µm. The trend of the frequency doubling signal with particle size is observed to determine whether phase matching can be achieved. Under the same test conditions, the intensity of the second harmonic generated by the sample under test is compared with the intensity of the second harmonic generated by the reference crystal KH₂PO₄ (KDP) to obtain the relative magnitude of the frequency doubling effect of the sample.

[0058] like Figure 5 As shown, the test results indicate that compound (H) 11 C4N2)CdI3 outputs a very strong 532 nm laser under 1064 nm laser irradiation. Its powder SHG coefficient is 6 times that of KH2PO4 (KDP) and it can achieve phase matching.

[0059] Example 4: Diffuse Reflectance Absorption Spectroscopy Test With sample 1 # As a representative, for (H) 11 Diffuse reflectance absorption spectroscopy of C4N2)CdI3 was performed using a PerkinElmer Lambda-750 UV-Vis-NIR spectrophotometer. The crystal sample was ground into powder, with BaSO4 used as a reference substrate. The test results are as follows: Figure 3 As shown, this indicates that compound (H) 11The crystal of (H C4N2)CdI3 has a wide transmittance range and has a high transmittance in a spectral range of 200-800 nm. The ultraviolet absorption cutoff wavelength is about 289 nm.

[0060] Example 5: Thermogravimetric analysis of the sample The sample 1 # was taken as a representative sample, and the (H 11 C4N2)CdI3 was subjected to thermogravimetric analysis on a Rigaku TG-DTA 8121 type thermogravimetric analyzer, and the results are shown in Figure 4 The figure shows that the crystal of (H 11 C4N2)CdI3 has high thermal stability and can be stabilized to 280°C. At this temperature, the weight loss is not more than 1%.

[0061] The above is only a few embodiments of the present application, and does not limit the present application in any form. Although the present application discloses the above preferred embodiments, it is not intended to limit the present application. Any skilled person in the art can make some changes or modifications to the above disclosed technical content without departing from the scope of the technical solution of the present application, which is equivalent to the equivalent embodiments, and belongs to the scope of the technical solution.

Claims

1. An organic-inorganic hybrid crystal, characterized in that, The chemical formula of the organic-inorganic hybrid crystal is (H 11 C4N2)CdI3, belonging to the monoclinic crystal system, space group 1. Cc The unit cell parameters are a = 14.3~14.5 Å, b = 7.1~7.3 Å, c = 13.7~13.9 Å, α = γ = 90°, β = 120~122°, Z = 4.

2. The organic-inorganic hybrid crystal according to claim 1, characterized in that, The cell parameters are: a = 14.36~14.38 Å, b = 7.13~7.15 Å, c = 13.77~13.79 Å, α = γ = 90°, β = 121.2~121.4°; Preferably, the cell parameters are: a = 14.368-14.369 Å, b =7.134~7.136 Å, c =13.777~13.779 Å.

3. The organic-inorganic hybrid crystal according to claim 1, characterized in that, The ultraviolet absorption cutoff wavelength of the organic-inorganic hybrid crystal is 285~295 nm; Preferably, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 289 nm; Preferably, the inorganic compound crystal has a powder SHG coefficient that is 3 to 12 times that of KH2PO4 under 1064 nm laser irradiation, and phase matching can be achieved; Preferably, the inorganic compound crystal has a powder SHG coefficient that is 6 times that of KH2PO4 under 2.05 μm laser irradiation, and phase matching can be achieved; Preferably, the inorganic compound crystal loses no more than 1% of its weight at 285°C.

4. The method for preparing the organic-inorganic hybrid crystal according to any one of claims 1-3, characterized in that, The organic-inorganic hybrid crystal was prepared by hydrothermal method, in which a mixture of raw materials containing piperazine ligand, cadmium, iodine, HI aqueous solution and water was crystallized at a crystallization temperature of 80℃~150℃ for no less than 6 hours.

5. The preparation method according to claim 4, characterized in that, In the raw material mixture, the molar ratio of piperazine ligand H2C4N2, cadmium (Cd), iodine (I), HI in the HI aqueous solution, and water is: H2C4N2: Cd: I: H2O =1: 0.05~5: 1~400: 1~400; Preferably, the molar ratio of piperazine ligand, cadmium, iodine, and water in the raw material mixture is: H2C4N2: Cd: I: H2O =1: 0.1~2: 5~100: 10~200; Preferably, the molar ratio of piperazine ligand, cadmium, iodine, and water in the raw material mixture is: H2C4N2: Cd: I: H2O =1: 0.3~0.8: 10~50: 50~150.

6. The preparation method according to claim 4, characterized in that, In the raw material mixture, the piperazine ligand is selected from at least one of piperazine, piperazine hydrochloride, piperazine iodate, piperazine bromate, piperazine carbonate, and piperazine phosphate; the cadmium element is selected from at least one of cadmium oxide, chromium chloride, cadmium bromide, chromium iodide, cadmium nitrate, cadmium carbonate, and cadmium sulfate; and the iodine is selected from at least one of chromium iodide and HI aqueous solution.

7. The preparation method according to claim 4, characterized in that, The specific steps are as follows: (a) Place the raw material mixture containing piperazine ligand, cadmium, iodine and water in a high-pressure reactor, seal it and crystallize it at a crystallization temperature of 80℃~150℃ for more than 24 hours. (b) After crystallization, the product obtained in step (a) is cooled to room temperature at a rate not exceeding 15℃ / h. The solid sample obtained after separation and drying is the organic-inorganic hybrid crystal. Preferably, the cooling rate in step (b) is 0.5~13℃ / h; Preferably, the cooling rate in step (b) is 0.5~6℃ / h.

8. A second-order nonlinear optical crystal material, characterized in that, The organic-inorganic hybrid crystal contains the organic-inorganic hybrid crystal according to any one of claims 1-3, or the organic-inorganic hybrid crystal prepared by the preparation method according to any one of claims 4-8.

9. A laser frequency converter, characterized in that, It contains the second-order nonlinear optical crystal material as described in claim 9.